Takeover Risk and the Market for Corporate Control: The Experience of British Firms in the 1970s and 1980s - Andrew P. Dickerson; Heather D. Gibson; Euclid Tsakalotos (University of Kent, Department of Economics, 1998)
This paper investigates the determinants of takeovers in a large sample of UK quoted companies. We focus on the channels through which the market for corporate control monitors company performance and discretionary managerial behaviour. Our results indicate that the market for corporate control disciplines poorly performing companies, and that this effect is quantitatively important: a one standard deviation increase in profitability is associated with a fall in the conditional probability of takeover of over 20%. However, we find no evidence that firms without apparent profitable investment opportunities are more likely to be taken over if managers increase investment or reduce dividends, contrary to the predictions of the free cash-flow theory of takovers.
Keywords: L1; G3; C41; 330; Takovers; Market for Corporate Control; Hazard Functions; Übernahme; Corporate Governance; Großbritannien